How to disseminate national recommendations for physical activity: a qualitative analysis of critical change agents in Germany - Laura Wolbring; Anne Kerstin Reimers; Claudia Niessner; Yolanda Demetriou; Steffen Christian Ekkehard Schmidt; Alexander Woll; Hagen Wäsche (BMC, 2021)
Abstract Background Physical activity recommendations are reached by only a small part of the population. A common problem is that research findings on public health-related topics such as physical activity promotion are oftentimes not translated into practice. The involvement of relevant stakeholders, such as change agents (role models, decision-makers, and/or knowledge mediators), is a common strategy to implement physical activity recommendations in specific settings, as they have the necessary knowledge of contextual factors. However, dissemination and implementation of physical activity recommendations are often prevented by focusing exclusively on the health sector and by underestimating the individual perceptions and needs of change agents. Therefore, the purpose of this study was to address the problem of how physical activity recommendations can be translated into practice through comprehensive consideration of the situation and context of change agents from various sectors of society at different administrative levels. This allows for deriving recommendations for action on how a national dissemination strategy of physical activity recommendations should be designed. Methods Qualitative expert interviews were conducted with change agents from different sectors of society and administrative levels in Germany (N = 21). Case selection took place via a sampling plan. The interviews were recorded, transcribed verbatim, and analysed by two trained researchers using qualitative content analysis. Results The change agents' perceived relevance of physical activity and physical activity promotion and their knowledge of physical activity recommendations varied across different sectors. Nine themes were identified covering the change agents' needs for the implementation of physical activity recommendations: strengthening of political will and cooperation, availability of public space for physical activity, change in awareness and health education, professional qualification, financial incentives, development of physical activity-promoting programmes and structures, provision of resources, bridging the theory-practice gap, and knowledge of physical activity recommendations. Conclusions This exploratory study contributes to the development of an evidence-based dissemination strategy of physical activity recommendations involving change agents from various sectors. Cross-sectoral needs and obstacles were identified indicating gaps that have to be addressed. Future research should choose practice-oriented approaches to develop dissemination strategies that are adapted to the needs of local contexts.